Broadband diffusion and firm performance in rural areas. Quasi-experimental evidence. - Canzian, Giulia; Poy, Samuele; Schüller, Simone (My University, 2015)
This article analyzes the causal impact of advanced broadband accessibility on firm performance. We exploit a unique local policy intervention of a staged broadband infrastructure installation across rural municipalities in the Province of Trento (Italy), generating a source of exogenous (spatial and temporal) variation in the provision of nextgeneration broadband technology (ADSL2+). Employing a difference-in-differences strategy and using longitudinal firm-level data on annual balance sheet information of corporate enterprises, we show that ADSL2+ availability is associated with a significant increase in annual sales turnover of about 40 percent and an increase in value added of roughly 25 percent over the period of two years. The positive effect is found to be rather stable for different lengths of treatment exposure and across industrial sectors. However, no significant effects are found with respect to number of employees. Placebo estimations support a causal interpretation of our results. Overall, established corporate enterprises in underserved rural and remote areas appear to profit considerably from enhanced broadband delivery programs in terms of economic performance.
Keywords: Informationstechnologie; Kommunikationstechnologie; Ländlicher Raum; Regionalentwicklung; Wirtschaftsentwicklung; Internet; Breitbandausbau; Standortentwicklung